KOMPOSISI HASIL TANGKAPAN PANCING ULUR YANG DIDARATKAN DI PELABUHAN PERIKANAN PANTAI (PPP) MUNCAR - Aditya Bramana; Liya Tri Khikmawati; Made Mahendra Jaya; Ari Gunawan (Aurelia Journal, 2022)
The fishery resources found in the waters of the Bali Strait are very high from small pelagic to large pelagic fish. The abundance of fishery resources in these waters makes fishermen choose the type of catch to be taken. The types of catches obtained by fishermen vary, this is influenced by the fishing gear used, one of which is handline fishing gear. This research was conducted from May to June 2021. Primary data collection was carried out by purposive sampling method. Researchers participate in fishing activities directly. From the results of the unloading activities of the catches of four fishing boats, the main types of catches on the ulur fishing boats are kenyar (Sarda orientalis), banyar cobs (Euthynnus affinis), and layur (Trichiurus lepturus).  Bycatch obtained from four fishing boats, there are seven types of fish, namely Lanjaman Shark (Carcharhinus falciformis), Squid (Loligo sp), Manta Ray (Mobula birostris), Blue Kite (Decapterus macarellus), Slengseng (Scomber australasicus), Yellowfin Tuna (Thunnus albacares), and Marlin Black (Istiompax indica).